AVALIAÇÃO DO DESENVOLVIMENTO NEUROPSICOMOTOR EM PREMATUROS COM ALTERAÇÕES ULTRA-SONOGRÁFICAS CEREBRAIS NO PERÍODO NEONATAL - Cunha, Roxana Desterro e Silva da (2007)
The scientific and technologic advances that occurred in the neonatal ITU over the last decades increased the survival rate of babies over and over more premature. Due to the occurency of possible sequelae inherent to this condition, it has been a bigger interest for de development of egress babies from these unites of treatment. The present study is retrospective, longitudinal, analytical of a control case, nested to a cohort. It proposes to evaluate the motor and cognitive development of premature babies who had brain ultrasound alterations at the neonatal period and the possible risk factors for its delay. It has been selected 99 premature children weighting 1800 grams or less in the birth and pregnancy age inferior to 37 weeks, submitted to a transfontanelar ultrasound in the neonatal period during their neonatal ITU (Intensive Therapy Unity) internment. The socio-economic, cultural, environmental, perinatal clinic events and mother characteristics were analysed. To evaluation of the neural, psychomotor development, the Denver II test was used. A sample made, in the majority, of corrected 12 months old children. The birth weight average was 1032 grams and the pregnancy average was 31,3 weeks. The ultrasonic alterations were present in 49, 4% of the children. In them, the periventricular leucomalacy was more frequent corrected one year old babies with alterations in the Denver II test. 34, 3% of the realized tests had unsatisfactory results. As risk factors for the development alteration, Ultrasonic alterations and low family incomes were significant for the study. . The positive predictive value of transfontanelar ultrasonic exams for the neural psychomotor development was 51,02% and the negative predictive value was 82% When the family incomes variable is added to the transfontanelar ultrasonic alterations, the positive predictive value increased to 90% and the negative predictive value decreased to 71,91%. It is believed that the variable family incomes added to the analysis is a good alternative to increase the prediction capacity development alterations of premature children with transfontanelar ultrasonic alterations.